Codex Tchacos 5 (CT 5) a Corpus Hermeticum XIII (CH XIII) - Sowińska, Agata (Vox Patrum, 2026)
The article presents a commented translation of the extant fragments from the Codex Tchacos, constituting the fifth text found in the codex. In Coptic, these fragments are identical to the analogous Hermetic verses from the treatise Corpus Hermeticum XIII. This article is a pilot part of the first commented Polish translation of Codex Tchacos (forthcoming).